PENGARUH BRAND LOVE, ADVERTISING, BRAND AUTHENTICITY, SERTA BRAND FAMILIARITY, TERHADAP BRAND EQUITY MELALUI BRAND SATISFACTION DAN BRAND TRUST PADA PENGUNJUNG KENTUCKY FRIED CHICKEN DI KOTA SAMARINDA - Suminto; Sarwo Edi Wibowo; Muhammad Arif Fadilah (Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the effect of Brand love, Advertising, Brand Authenticity and Brand Familiarity on Brand Equity through Brand Satisfaction and Brand Trust of Kentucky Fried Chicken visitors in Samarinda City. This study uses a quantitative approach with path analysis tools processed with IBM SPSS Statistics 23 software and Structural Equation Modeling (SEM) with IBM Amos 23 software. This study used a sample of 186 respondents with a measurement scale using a Likert scale with a score of 1 - 5. In this study, validity and reliability tests, classical assumption tests, model fit tests and hypothesis testing were carried out. Based on the results of hypothesis testing, it can be proven that 4 of the 14 hypotheses found are not significant such as Brand Love to Brand Satisfaction, Brand Love to Brand Equity, and Brand Authenticity to Brand Equity. While the other 10 are significant, namely the relationship between Advertising to Brand Satisfaction, Brand Authenticity to Brand Satisfaction, Brand Familiarity to Brand Satisfaction, Advertising to Brand Trust, Brand Authenticity to Brand Trust, Brand Familiarity to Brand Satisfaction. Then Brand Satisfaction to Brand Trust, Brand Satisfaction to Brand Equity, Brand Trust to Brand Equity, Advertising to Brand Equity.